Analysis of the Influence of Instagram and TikTok on Motivation and Learning Outcomes of High School Students in Indonesia - Mayasari, Renni; Agoestyowati, Redjeki; Rasyad, Rizky Zakariyya (International Journal Education and Computer Studies (IJECS), 2025)
In the digital era, education is undergoing a profound transformation with the emergence of social media as a powerful learning tool. This study explores the impact of Instagram and TikTok on student learning in Indonesia through a case study approach conducted at three high schools in Jakarta, Surabaya, and Bandung. The research aims to analyze how these social media platforms influence students' learning motivation, academic performance, and character development. Employing a qualitative methodology, data were collected through in-depth interviews, classroom observations, and content analysis of social media materials. The findings reveal that Instagram and TikTok significantly boost learning motivation among 78% of the 90 eleventh-grade students surveyed and improve academic performance by 15-25% in subjects like chemistry and sociology. However, challenges such as distraction from non-educational content (reported by 60% of students) and inadequate digital literacy skills pose significant hurdles. Additionally, while positive content fosters values like respect and responsibility, exposure to inappropriate material risks undermining character development. This study recommends the strategic integration of social media into the curriculum with clear guidelines and teacher guidance, alongside digital literacy training, to maximize benefits and mitigate negative impacts. These insights offer a pathway for educators and policymakers to harness the potential of digital platforms in enhancing education while addressing their inherent challenges.